Demand response performance and uncertainty: A systematic literature review. (May 2022) - Silva, C.; Faria, P.; Vale, Z.; Corchado, J.M.
Abstract: The present review has been carried out, resorting to the PRISMA methodology, analyzing 218 published articles. A comprehensive analysis has been conducted regarding the consumer's role in the energy market. Moreover, the methods used to address demand response uncertainty and the strategies used to enhance performance and motivate participation have been reviewed. The authors find that participants will be willing to change their consumption pattern and behavior given that they have a complete awareness of the market environment, seeking the optimal decision. The authors also find that a contextual solution, giving the right signals according to the different behaviors and to the different types of participants in the DR event, can improve the performance of consumers' participation, providing a reliable response. DR is a mean of demand-side management, so both these concepts are addressed in the present paper. Finally, the pathways for future research are discussed. Highlights: Addressing consumer response uncertainty in demand response events. Fostering consumers participation in demand response programs. The importance of enhancing the performance of active consumers. Understanding consumers' motivations under demand response participation.